Investment development of agriculture in the region - Isaeva Anastasia Alexandrovna (International Journal on Orange Technologies, 2019)
Attracting investment in agriculture remains one of the key in the development of the economy. The article analyzes the investment attractiveness of the agricultural sector of the Ulyanovsk region, as well as specific indicators of competitiveness of the agro-industrial complex of the region.